Challenging Gendered Social Norms: Educational Insights from Confucian Classics. Issue 3 (3rd July 2019) - Tan, Charlene
ABSTRACT: This article highlights the salient educational insights concerning the roles and identities of women from four Confucian classics known as the Four Books for Women ( Nü sishu ). Written by women, the texts collectively challenge three prevailing gendered social norms: the deprivation of education for girls, the necessity of the wife to obey her husband all the time, and the assumption of the moral inferiority of women. Correspondingly, the authors argue for the right of girls to schooling, the need for the wife to remonstrate with her husband, and the potential of women to become moral exemplars and sages. The authors legitimise their arguments by drawing on selected Confucian teachings pertaining to gender mutuality, normative behaviours, innate moral nature and self-cultivation. Going beyond the traditional roles of women as wives, mothers and daughters-in-law, the texts envisage women as educated and ethical role models who complement the men in advancing the Way.